Design of a fragment crystallizable-engineered tetravalent bispecific antibody targeting programmed cell death-1 and vascular endothelial growth factor with cooperative biological effects - Tingting Zhong; Lingzhi Zhang; Zhaoliang Huang; Xinghua Pang; Chunshan Jin; Wenrong Liu; Juan Du; Wen Yin; Na Chen; Jing Min; Michelle Xia; Baiyong Li (iScience)
Summary: Clinical studies have shown that combination therapy of PD-1 and VEGF antibodies significantly improves clinical benefit over PD-1 antibody alone in certain settings. Ivonescimab, an on-market tetravalent anti-PD-1/VEGF bispecific antibody, was designed to improve efficacy and safety over combo therapy. In this study, the mechanism of action is investigated. In the presence of VEGF, ivonescimab forms soluble complexes with VEGF dimers, leading to the enhanced binding avidity of ivonescimab to PD-1 therefore promoting its increased potency on PD-1/PD-L1-signaling blockade. Likewise, PD-1 binding enhanced ivonescimab binding to VEGF, therefore enhancing VEGF-signaling blockade. Furthermore, ivonescimab treatment demonstrated statistically significant anti-tumor response in vivo. Moreover, ivonescimab contains Fc-silencing mutations abrogating FcγRI/IIIa binding and showed significantly reduced effector function in vitro which is consistent with the better safety profile of ivonescimab in monkeys and humans. Briefly, ivonescimab displays unique cooperative binding and promotes the increased in vitro functional bioactivities with a favorable safety profile.